2014
DOI: 10.1093/nar/gku1155
|View full text |Cite
|
Sign up to set email alerts
|

GEM2Net: from gene expression modeling to -omics networks, a new CATdb module to investigate Arabidopsis thaliana genes involved in stress response

Abstract: CATdb (http://urgv.evry.inra.fr/CATdb) is a database providing a public access to a large collection of transcriptomic data, mainly for Arabidopsis but also for other plants. This resource has the rare advantage to contain several thousands of microarray experiments obtained with the same technical protocol and analyzed by the same statistical pipelines. In this paper, we present GEM2Net, a new module of CATdb that takes advantage of this homogeneous dataset to mine co-expression units and decipher Arabidopsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…This results in the production of substances toxic to herbivores or in making the plant meal indigestible. To test the hypothesis that the overall transcriptomic response of insect-stimulated Dionaea traps resembles defined stress-related responses known from noncarnivorous plants, we performed an interspecies comparison of active Dionaea plants to known coexpressed gene clusters in A. thaliana (Zaag et al 2015). Taking advantage of the Complete Arabidopsis Transcriptome MicroArray (CATMA) gene expression reference database for Arabidopsis, we identified a diverse pattern of validated abiotic and biotic stress-related gene clusters (Supplemental Table S17) up-regulated in active traps.…”
Section: Active Traps Display Conserved Stress Signalsmentioning
confidence: 99%
“…This results in the production of substances toxic to herbivores or in making the plant meal indigestible. To test the hypothesis that the overall transcriptomic response of insect-stimulated Dionaea traps resembles defined stress-related responses known from noncarnivorous plants, we performed an interspecies comparison of active Dionaea plants to known coexpressed gene clusters in A. thaliana (Zaag et al 2015). Taking advantage of the Complete Arabidopsis Transcriptome MicroArray (CATMA) gene expression reference database for Arabidopsis, we identified a diverse pattern of validated abiotic and biotic stress-related gene clusters (Supplemental Table S17) up-regulated in active traps.…”
Section: Active Traps Display Conserved Stress Signalsmentioning
confidence: 99%
“…Meta-analysis has been used in other fields to synthesize transcriptomic data, and should also be more widely implemented for plant differential response data. Shaik and Ramakrishna (2013) and Zaag et al (2015) synthesized DEG microarray studies on biotic and abiotic stress responses in Arabidopsis, and identified genes that were differentially expressed in response to each stress. Although these approaches were each shown to be effective in various ways, for example in assisting with functional annotations and visualizing co-expression relationships, the disadvantages of these approaches are that they do not weight studies based on precision (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Zaag et al . () used a model‐based clustering approach to find and visualize co‐expressed genes involved in the response of Arabidopsis to stress; this approach was applied to each of 18 stress categories. However, these approaches are limited because they do not account for differential variance among experiments, nor do they model methodological and biological covariates within or across stress categories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaussian mixture models were relevant for microarray data and were applied with success on several datasets [35,36]. For RNAseq data, which are discrete, Rau et al [16] first concluded that normalized expression profiles modelled with a Poisson mixture are relevant for co-expression analysis.…”
Section: Selection Of the Statistical Methodsmentioning
confidence: 99%